Compilation of a regionally extended inter-country input-output table and its application to global value chain analyses - Bo Meng; Norihoko Yamano (Journal of Economic Structures, 2017)
Studies on the rise of global value chains (GVCs) have attracted a great deal of interest in the recent economics literature. However, due to statistical and methodological challenges, most existing researches ignore domestic regional heterogeneity in assessing the impact of joining GVCs. GVCs are supported not only directly by domestic regions that export goods and services to the world market, but also indirectly by other domestic regions that provide parts, components, and intermediate services to final exporting regions. To better understand the nature of a country's position and degree of participation in GVCs, we need to fully examine the role of individual domestic regions. Understanding the domestic components of GVCs is especially important for larger economies such as China, the USA, India, and Japan, where there may be large variations in economic scale, geography of manufacturing, and development stages at the domestic regional level. This paper proposes a new framework for measuring domestic linkages to global value chains. This framework measures domestic linkages by endogenously embedding a target country's (e.g., China or Japan) domestic inter-regional input-output tables into the OECD inter-country input-output model. Using this framework, we can more clearly understand how global production is fragmented and extended internationally and domestically.
Keywords: 330; Input-output; Global value chains; Regional heterogeneity